Organizational Justice and Employee Sustainability: The Mediating Role of Organizational Commitment - Mehreen Fatima; Zeeshan Izhar; Zaheer Abbas Kazmi (SEISENSE Journal of Management)
Purpose- The primary purpose of the study is to determine the impact of organizational justice (OJ) on employee sustainability. Along with that, it also describes how organizational commitment mediates this direct relationship. This study includes all dimensions of OJ which are distributive, procedural and interactional (interpersonal & informational) within the context of a developing country (Pakistan).